Determinism of the symmetry of a single-crystalline surface of interface at obtaining 0D- and 2D-structues of noble metals and indium on silicon - Karbivska, L.I.; Karbivskyy, V.L.; Romanskyy, A.O. (Успехи физики металлов, 2019)
The review article deals with ‘quantum engineering’ of growing of silver films on semiconductor substrates that allows obtaining new forms of matter. The results on the energy dispersion of electron states in epitaxial Ag (111) films obtained on Si (001) and Si (111) are presented.